HAGUE, Ian. Comics and the senses: a multisensory approach to comics and graphic novels. New York: Routledge, 2014. 214p. - Gomes, Ivan Lima (História, histórias, 2016)
HAGUE, Ian. Comics and the senses: a multisensory approach to comics and graphic novels. New York: Routledge, 2014. 214p.